Investigating novel cationic polymers for siRNA delivery for treatment of allergic disease - Almughem, Fahad (2018)
Spleen tyrosine kinase (Syk) is an enzyme which plays a prominent role in IgE-dependent signal transduction in type 1 hypersensitivity reactions. Due to the important role of Syk in the early signalling cascade in mast cells and basophils for inducing allergic reaction, it could be a suitable target for the treatment of allergy. In this project, the efficacy of Syk gene silencing in the inhibition of mast cell degranulation and cytokine induction by small interfering RNA (siRNA) in vitro was evaluated. The evaluation of the inhibition of Syk function was assessed by two novel rat basophil leukaemia (RBL-2H3) derived reporter cell lines which are Neuropeptide Y-Red Fluorescent Protein fusion (NPY–mRFP) and Nuclear factor of activated T-cells-DsRed (NFAT-DsRed) reporter cell lines. In NPY–mRFP reporter cells, red fluorescent protein (RFP) is targeted and stored in the granules and released into the medium during degranulation upon appropriate IgE-dependent stimulation of the cells. In NFAT-DsRed reporter cell, DsRed can be expressed upon appropriate IgE-dependent stimulation of the cells resulting in translocation of NFAT from the cytosol to the nucleus and reporter gene expression. Novel cationic polymers in this project were evaluated for the delivery of siRNA. The first polymer was AGMA29, an amphoteric linear polyamidoamine polymer which has been reported to be useful for gene delivery and with a low toxicity. In addition, two modified poly(glycerol adipate) (PGA) variants were used. PGA is a polyester which can be derivatised with a variety of substituents to make cationic polymers. Derived polymers PGA-50% lysine (PGA-50% Lys) and PGA-20% histidine (PGA-20% His) were evaluated in this work to determine the size, efficacy and toxicity of polyplexes used in the Syk siRNA delivery. Using optimised polyplex resulted in the knockdown of the Syk function in the release of RFP in NPY–mRFP and the DsRed induction in NFAT-DsRed reporter cell lines, optimal calcium concentration and media used were determined. A new method was established for measuring the release of RFP in the NPY–mRFP cells, which could be used for detecting allergic reactions. The results showed that the polyplexes could be used for transfection when they were prepared in deionised water. 5 RU/Nt of AGMA29/Syk siRNA H polyplex resulted in a 31% decrease in the release of RFP in NPY-mRFP cell lines in comparison to untreated cell or scrambled siRNA. PGA-50% Lys/Syk siRNA H at 10AA/Nt ratio resulted in a 31% decrease in the release of RFP in NPY-mRFP cell lines in comparison to untreated cell and 24% in comparison to scrambled siRNA. The final finding from evaluation of Syk mRNA by RT-qPCR showed that the Syk mRNA knockdown at 5 RU/Nt of AGMA29/siRNA H was low (~26%) after 48 hr of the transfection. Interestingly, almost complete knockdown of Syk mRNA by PGA-50% Lys/Syk siRNA H was achieved at 5,10, and 20 AA/Nt ratios. This work therefore contributes to the exploration of a novel polyester based polymer for siRNA gene therapy and compares it with a polyamidoamine based polymer. From the results obtained it is concluded that the novel polyester based polymer for siRNA delivery is safe, effective in the transfection of hard to transfect cells and could be used for future siRNA in vivo gene silencing applications.